Sex differences in musculoskeletal injury and disease risks across the lifespan: Are there unique subsets of females at higher risk than males for these conditions at distinct stages of the life cycle? - Hart, David A. (Frontiers in Physiology, 2023)
Sex differences have been reported for diseases of the musculoskeletal system (MSK) as well as the risk for injuries to tissues of the MSK system. For females, some of these occur prior to the onset of puberty, following the onset of puberty, and following the onset of menopause. Therefore, they can occur across the lifespan. While some conditions are related to immune dysfunction, others are associated with specific tissues of the MSK more directly. Based on this life spectrum of sex differences in both risk for injury and onset of diseases, a role for sex hormones in the initiation and progression of this risk is somewhat variable. Sex hormone receptor expression and functioning can also vary with life events such as the menstrual cycle in females, with different tissues being affected. Furthermore, some sex hormone receptors can affect gene expression independent of sex hormones and some transitional events such as puberty are accompanied by epigenetic alterations that can further lead to sex differences in MSK gene regulation. Some of the sex differences in injury risk and the post-menopausal disease risk may be “imprinted” in the genomes of females and males during development and sex hormones and their consequences only modulators of such risks later in life as the sex hormone milieu changes. The purpose of this review is to discuss some of the relevant conditions associated with sex differences in risks for loss of MSK tissue integrity across the lifespan, and further discuss several of the implications of their variable relationship with sex hormones, their receptors and life events. .